2021
DOI: 10.1113/jp282430
|View full text |Cite
|
Sign up to set email alerts
|

A novel ion conducting route besides the central pore in an inherited mutant of G‐protein‐gated inwardly rectifying K+ channel

Abstract: G‐protein‐gated inwardly rectifying K+ (GIRK; Kir3.x) channels play important physiological roles in various organs. Some of the disease‐associated mutations of GIRK channels are known to induce loss of K+ selectivity but their structural changes remain unclear. In this study, we investigated the mechanisms underlying the abnormal ion selectivity of inherited GIRK mutants. By the two‐electrode voltage‐clamp analysis of GIRK mutants heterologously expressed in Xenopus oocytes, we observed that Kir3.2 G156S perm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Studies with the K ir 3.2 S148F mutant showed that application of 1‐mM GA did not induce a change in the current amplitude (Figure 2f). Mutation of K ir 3.2 Ser148 to Phe alters its ion selectivity (Chen et al, 2022), suggesting a conformational change in the pore‐forming region. GA may therefore be no longer capable of modulating the activity of this mutant channel because of the overall structural difference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with the K ir 3.2 S148F mutant showed that application of 1‐mM GA did not induce a change in the current amplitude (Figure 2f). Mutation of K ir 3.2 Ser148 to Phe alters its ion selectivity (Chen et al, 2022), suggesting a conformational change in the pore‐forming region. GA may therefore be no longer capable of modulating the activity of this mutant channel because of the overall structural difference.…”
Section: Resultsmentioning
confidence: 99%
“…Site‐directed mutagenesis of K ir 3.1 and K ir 3.2 mutants was performed as previously described (Chen et al, 2022). Briefly, PfuUltra II Fusion HS DNA Polymerase kit (Agilent Technologies, Santa Clara, CA, USA) and the primers (Table S1) were used to introduce point mutation in K ir 3.x channels by polymerase chain reaction and were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have revealed that mice exhibit impairments in learning and memory when the Epha6 protein is knocked out ( Savelieva et al, 2008 ; Farini et al, 2020 ). Kcnj6, an essential component of the presynaptic membrane, serves as a key regulatory target for hippocampal neuron excitability and synaptic plasticity ( Alfaro-Ruiz et al, 2021 ; Thompson and Satin, 2021 ; Chen et al, 2022 ). These up-regulated genes contribute to the regulation of synapse structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes were isolated from female Xenopus laevis as previously described ( Chen et al, 2022 ). Frogs were purchased from Watanabe Zoushoku (Hyogo, Japan) and housed at 18°C in the animal facility of Wakayama Medical University.…”
Section: Methodsmentioning
confidence: 99%